Liberation Theology According to Abdurrahman Wahid and Gustavo Gutierrez - Sangkot Sirait (Jurnal Theologia, 2020)
This paper tells the thoughts of two religious figures who are concerned with talking about religion and humanity. These two figures are Abdurrahman Wahid and Gustavo Gutiérrez. The question that will be answered here is how the concept of the liberation of the two figures and where the difference lies and their implications for real life. The issues discussed here are related to theology, more popularly called liberation theology. The method used in this research is to read and examine the work of each of the two figures, both works that are called primary or secondary. After that, the concepts are compared according to their respective contexts. From the results of research on their works, an understanding is obtained that the theology of liberation is inspired by the real conditions of society that are of concern, both in terms of poverty and opportunity. Therefore, according to the two figures, religion must be able to solve the problem, it means that religion practised not only as a doctrine but also humanity. Action work of people who profess religion is needed to solve community problems. There are differences in the approaches of the two figures, namely Gutiérrez is more focused directly involved, while Wahid besides being directly involved, but also with a cultural approach and changing the way people think. The difference between the two approaches has implications for the process of change, namely Gutiérrez is more revolutionary mechanistic, while Wahid is more cultural and evolutionary